2005
DOI: 10.1007/s00122-005-0020-5
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution physical mapping reveals that the apospory-specific genomic region (ASGR) in Cenchrus ciliaris is located on a heterochromatic and hemizygous region of a single chromosome

Abstract: An apomictic mode of reproduction known as apospory is displayed by most buffelgrass (Cenchrus ciliaris) genotypes, but rare sexual individuals have been identified. Previously, intraspecific crosses between sexual and aposporous genotypes allowed linkage to be discovered between the aposporous mode of reproduction and nine molecular markers that had been isolated from an aposporous relative, Pennisetum squamulatum. This region was described as the apospory-specific genomic region (ASGR). We now show an ideogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 34 publications
6
65
0
Order By: Relevance
“…Several hypotheses have been formulated to explain the causes of the block of recombination described in apomictic systems (Grimanelli et al 1998;Ozias-Akins et al 1998;Labombarda et al 2002;Goel et al 2003); among these the physical location of the ACL in heterochromatindense pericentromeric regions that are known to be recombinationally suppressed appears worthy of investigation. Recent results obtained for C. ciliaris seem to confirm this hypothesis since the apomixis locus of this species is located near the centromere in a heterochromatin-rich region (Akiyama et al 2005). Several characteristics associated with heterochromatin have been observed at the same locus of P. squamulatum, although it is not located close to the centromere (Akiyama et al 2004).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several hypotheses have been formulated to explain the causes of the block of recombination described in apomictic systems (Grimanelli et al 1998;Ozias-Akins et al 1998;Labombarda et al 2002;Goel et al 2003); among these the physical location of the ACL in heterochromatindense pericentromeric regions that are known to be recombinationally suppressed appears worthy of investigation. Recent results obtained for C. ciliaris seem to confirm this hypothesis since the apomixis locus of this species is located near the centromere in a heterochromatin-rich region (Akiyama et al 2005). Several characteristics associated with heterochromatin have been observed at the same locus of P. squamulatum, although it is not located close to the centromere (Akiyama et al 2004).…”
Section: Discussionmentioning
confidence: 82%
“…In a recent paper, Goel et al (2003) reported for the first time the FISH-aided localization of the apomixis locus on metaphase chromosomes and they claimed that its vicinity to the centromere in Cenchrus ciliaris and to centromeric repeats in P. squamulatum could cause the repression of recombination at the same locus in these species. Further FISH analyses on pachytene chromosome preparations of the same species are in favour of these assumptions (Akiyama et al 2004;Akiyama et al 2005;Ozias-Akins et al 2003). FISH using pachytene chromosomes as targets offers superior spatial resolution of adjacent probes compared to metaphase chromosomes and display clearly the dense heterochromatic regions on the chromosomes and so allow the assignment of a probe position in relation to the structural organization of its surrounding chromosome context (de Jong 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This asexual reproduction provides the advantage of rapid multiplication allowing the development of a significant aboveground yield and consequently the formation of an extremely dense ground cover by C. ciliaris (Ozias-Akins et al 2003;Akiyama et al 2005;Miles 2007;Ozias-Akins and Van Dik 2007;Singh et al 2007). Asexual reproduction may have benefits in stable environments, while sexual reproduction offers a net advantage by allowing more rapid generation of genetic diversity allowing adaptation to a changing environment.…”
Section: Facultative Nature Of Apomixis In Cenchrus Ciliarismentioning
confidence: 99%
“…Cytogenetic investigations of tetraploid C. ciliaris have demonstrated that the ASGR is located near the centromere in a genomic region that is hemizygous and heterochromatic (condensed part of chromatin genetically inactive) (Goel et al 2003(Goel et al , 2006Ozias-Akins et al 2003;Akiyama et al 2005). The ASGR-carrier chromosome has a unique morphological characteristic when compared with other chromosomes in the genome (Akiyama et al 2005) and is~20 Mb larger than its presumed homologous chromosomes (Goel et al 2003;Akiyama et al 2005). Goel et al (2003) suggest that chromosome structure, proximity to centromere and hemizygosity (the state of having only one copy of a gene in the diploid cell instead of the usual two copies) may all play a role in the low recombination rates in the ASGR.…”
Section: Facultative Nature Of Apomixis In Cenchrus Ciliarismentioning
confidence: 99%
See 1 more Smart Citation